Bicycling renaissance in North America? Recent trends and alternative policies to promote bicycling. - Pucher, John; Komanoff, Charles; Schimek, Paul (My University, 1999)
Over the past two decades, the number of bicycle trips in the United States has doubled. Since 48% of trips by all modes in American cities are shorter than three miles, the potential for further growth in bicycling seems enormous. So far, efforts to promote bicycling have focused on building bike paths and bike lanes. Although necessary, separate cycling facilities must be complemented by a comprehensive program to make all roads bikeable, through both physical adaptations and enforcement of cyclists right to use the road. It seems likely that cycling will continue to grow in North America, but that its mode share will remain far lower than levels in northern Europe. Bicycling in Canada and especially the United States is impeded by the lack of a tradition of cycling for utilitarian purposes and by the marginal legal, cultural and infrastructure status of cyclists in both countries automobile-based transport systems. As long as car use remains cheap and transportation policy remains dominated by motoring, bicycles will continue to be used primarily for recreation and not for daily urban travel in North America. difu
Keywords: Fahrradverkehr; Fahrradweg; Freizeitverkehr; Verkehrspolitik; Verkehrsmittelwahl; Verkehrssicherheit; Individualverkehr; Fahrradförderung; Fahrradnutzung; Radverkehrsanteil; Fahrradinfrastruktur; Radfahrstreifen; Radverkehrsanlage; Alltagsverkehr